Pengaruh Lingkungan Toko dan Faktor Situasional terhadap Perilaku Pembelian Tak Terencana Pada Matahari Department Store Denpasar - Widiartaka, Wayan Agus; Purnami, Ni Made (E-Jurnal Manajemen, 2014)
The purpose of this study was to determine the effect of  store environment and situational factor on impulse buying behavior at Matahari Department Store Denpasar. The research conducted in the city of Denpasar by taking subjects in Matahari Department Store Denpasar. Amount of sample in this study is 120 sample with purposive technic sampling. Data were collected with questionnaires  and multiple regression analysis. Based on the result from this study, find that store environment and situational factor has significant and positive influence on the impulse buying behavior.
Keywords: Store environment; Situational factor; Impulse Buying Behavior